Parvularcula marina sp. nov., isolated from surface water of the South China Sea, and emended description of the genus Parvularcula. Issue 8 (21st June 2019) - Sun, Lin-Lin; Dang, Yan-Ru; Li, Yi; Qin, Qi-Long; Su, Hai-Nan; Li, Ping-Yi; Chen, Xiu-Lan; Zhang, Yu-Zhong; Zhang, Xi-Ying
Abstract : A Gram-stain-negative, aerobic, flagellated, rod-shaped bacterial strain, SM1705 T, was isolated from a surface seawater sample collected from the South China Sea. The strain grew at 10–40 °C and with 0.5–13.0 % (w/v) NaCl. It hydrolysed Tweens 20, 40 and 60, but did not hydrolyse starch or Tween 80 nor reduce nitrate to nitrite. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain SM1705 T was affiliated with the genus Parvularcula, sharing the highest sequence similarity (96.0 %) with type strain of Parvularcula bermudensis and forming a coherent branch together with the latter within the clade of Parvularcula . The major cellular fatty acids were identiﬁed as summed feature 8 (C18 : 1 ω 7 c and/or C18 : 1 ω 6 c ), C16 : 0 and C18 : 0 . Polar lipids included three unidentified glycolipids and one unidentified lipid. The major respiratory quinone of strain SM1705 T was Q10. The genomic DNA G+C content of strain SM1705 T was 59.3 mol%. Based on the polyphasic evidence presented in this paper, strain SM1705 T represents a novel Parvularcula species, for which the name Parvularcula marina sp. nov. is proposed. The type strain is SM1705 T (=KCTC 62795 T =MCCC 1K03505 T =CCTCC AB 2018345 T ).